Frequency synchronization enhancement in wireless sensor network using cheetah chase algorithm - Goudhaman, M.; Sasikumar, S.; Vanathi, N. (International Journal of Engineering and Technology, 2020)
Frequency synchronization is a cutting edge framework for any distributed systems. Wireless sensor networks have risen as an imperative and promising exploration territory in the current years. Frequency synchronization is an imperative for some, sensor organize applications that require extremely exact mapping of assembled sensor information with the frequency of the occasions happened. Biologically inspirited, innovative swarm intelligence algorithms are the most unique algorithms for enhancement. In this proposed work, new population based nature-impelled metaheuristic optimization algorithm, named Cheetah Chase Algorithm (CCA), is presented for upgrading the frequency synchronization in the distributed environment. Â Â